2016
DOI: 10.1002/hfm.20692
|View full text |Cite
|
Sign up to set email alerts
|

Effective human utilization in an original equipment manufacturing (OEM) industry by the implementation of agile manufacturing: A POLCA approach

Abstract: Agile manufacturing (AM) has been recognized as an international strategy for improving industrial competitiveness. Agility refers to the ability of an organization to adapt to changes within its environment and to utilize them for earning profit and constituting a major item of expense for any organization, having a palpable effect on its profitability. Manpower utilization is considered as one of the important attributes affecting the organization's ability to be agile. In other words, an effective manpower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Similarly, while there have been several case study implementations of POLCA reported in the literature (e.g. Krishnamurthy & Suri, 2009;Riezebos, 2010;Ajay Guru Dev et al, 2017), the accuracy of the earliest release dates calculated by the HL/MRP system remains unclear; it is not even clear whether this element has been implemented in prior work. In other words, it remains unclear whether authors have actually implemented POLCA in its entirety.…”
Section: Discussion Of the Polca Literaturementioning
confidence: 99%
“…Similarly, while there have been several case study implementations of POLCA reported in the literature (e.g. Krishnamurthy & Suri, 2009;Riezebos, 2010;Ajay Guru Dev et al, 2017), the accuracy of the earliest release dates calculated by the HL/MRP system remains unclear; it is not even clear whether this element has been implemented in prior work. In other words, it remains unclear whether authors have actually implemented POLCA in its entirety.…”
Section: Discussion Of the Polca Literaturementioning
confidence: 99%